HAK ASASI MANUSIA (HAM) DALAM PERSPEKTIF ALQURAN - Aminah, Sitti (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2010)
This article copes with basic human rights from Qurâ€™anic perspective. This study shows that basic human rights in Qurâ€™an is termed huquq insaniyah. The principles of basic human rights can be explored by three terms, al-istiqrÄr, the right to live on earth until death; al-istimtÄâ€˜, the right to explore resources; and al-karÄmah. The last term refers to individual dignity yet with social implication, since individual dignity will be realized only in its relationship with others who recognize the dignity. So, this notion results in the right of equality. This term also necessitates the right of freedom where nobody is entitled to humiliate others.